Menajemen Sistem Informasi PT. Telkomsel Plasa - Dodi Hendri Syahputra; Fajar Dwi Ananda; Pazur Rohman Tri Asmoro; Fikri Haikal; Sepriano Sepriano (Journal on Education, 2023)
Field Work Practice (PKL) is a means of self-actualization of some skills or skills, both soft skills and hard skills that have been acquired during lectures, applied in an agency or company for several months. In this street vendor report, several work implementation activities are presented, findings of obstacles or problems and proposed solutions to obstacles or problems encountered at the PT.Plasa Telkom Group Jambi Agency for 2 months, namely August 29 2022 to October 28 2022. Placement of street vendors in this agency the author is placed in the Data Management Help Desk work area in this division, ensuring that the data administration process is reliable, easily accessible, and up-to-date in terms of time. This process includes the acquisition, validation, storage and protection, monitoring and careful processing of necessary data. Based on the implementation of Field Work Practices at PT.Plasa Telkom Group Jambi, it can be concluded that the author gets an overview of the application of knowledge or theory that has been obtained in lectures, gains new experience in adapting to the world of work by communicating well and the author gains insight and knowledge about the world of work.